2017
DOI: 10.1039/c7ra02286g
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of orange G and methylene blue from aqueous solutions using a Co(ii) coordination polymer

Abstract: A Co(ii) coordination polymer acts as a sponge for organic dye molecules, removing them from aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…An analysis of the crystal structure reveals that in addition to the PdMOP-like truncated tetrahedral pores, there are two additional pores that give rise to channels through the framework (see Figure ). The orange-colored product started turning light green during filtration and a darker green during activation as a result of solvent removal that prompts a phase transition reported to occur on the surface of the crystals. , The PXRD data supports this phase transition, with significant differences between the pre- and postactivation diffractograms. Since the phase transition was reported to be limited to the surface, we carried out PXRD (Figure ), TGA (Figure S3), and FTIR spectroscopy (Figure S4), along with sorption measurements, anticipating that the core Co Sponge may remain accessible to probing gas molecules.…”
Section: Resultssupporting
confidence: 82%
“…An analysis of the crystal structure reveals that in addition to the PdMOP-like truncated tetrahedral pores, there are two additional pores that give rise to channels through the framework (see Figure ). The orange-colored product started turning light green during filtration and a darker green during activation as a result of solvent removal that prompts a phase transition reported to occur on the surface of the crystals. , The PXRD data supports this phase transition, with significant differences between the pre- and postactivation diffractograms. Since the phase transition was reported to be limited to the surface, we carried out PXRD (Figure ), TGA (Figure S3), and FTIR spectroscopy (Figure S4), along with sorption measurements, anticipating that the core Co Sponge may remain accessible to probing gas molecules.…”
Section: Resultssupporting
confidence: 82%
“…The modularity, tunability, and permanent porosity of these materials make them valuable for a wide range of applications . MOFs have shown potential for the adsorption and photocatalytic degradation of gaseous and aqueous pollutants but are generally limited to the solid phase owing to their insolubility . Since MOPs may be soluble in aqueous or organic solvents, it is possible to study host – guest interactions homogeneously in the solution phase, an approach that has historically prompted their use as nanovessels for chemical reactions. , To date, only a limited number of studies have demonstrated their capacity for polyfluorinated compounds, organic dye, and anion pollutant adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) and porous coordination polymers (CPs) have unique properties including high surface area and structural flexibility, which have endowed them widespread application ranging from gas storage and separations, chemical sensing, drug delivery, to catalysis. , They have received considerable attention as powerful sorbents for different types of hazardous materials, namely because of their well-defined pore structures, high porosity, and tunable chemical properties. Therefore, the adsorption and recycling of organic dyes using MOFs and derived materials have become hot research topics. Generally, the adsorption performance of porous MOFs is closely associated with their high specific surface area, size and shape of pores, and presence of adjustable functional groups, thus allowing the use of MOFs as promising materials for the removal of dyes from wastewater. For example, a high adsorption capacity of MOF-235 was reported for cationic and anionic dyes, while methylene blue (MB) and methyl orange (MO) can be efficiently adsorbed by UiO-66, MIL-100­(Cr), and MIL-100­(Fe) .…”
Section: Introductionmentioning
confidence: 99%